2022
DOI: 10.1212/wnl.0000000000013066
|View full text |Cite
|
Sign up to set email alerts
|

Seizure Outcome After Surgery for MRI-Diagnosed Focal Cortical Dysplasia

Abstract: Objective:Focal cortical dysplasia (FCD) has been associated with poorer post-surgical seizure outcomes compared to other pathologies. FCD surgical series have been assembled on the basis of a histological diagnosis, including patients with abnormal as well as normal pre-operative MRI. However, in clinical workflow, patient selection for surgery is based on pre-operative findings, including MRI. We performed a systematic review and meta-analysis of the literature to determine the rate and predictors of favorab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…Persistent seizures in childhood, as well as the long-term usage of multiple antiepileptic drugs, have significant negative effects on children's growth, development, and cognitive functions. Previous studies have shown ( 5 7 ) that early surgery and the complete resection of the epileptogenic zone draw support from the plasticity of brain development to provide more opportunities for nerve cells to compensate, which is more beneficial for postoperative recovery and to improve the quality of life in children ( 16 ). We obtained consistent results from the analysis of clinical data that complete resection was beneficial for patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persistent seizures in childhood, as well as the long-term usage of multiple antiepileptic drugs, have significant negative effects on children's growth, development, and cognitive functions. Previous studies have shown ( 5 7 ) that early surgery and the complete resection of the epileptogenic zone draw support from the plasticity of brain development to provide more opportunities for nerve cells to compensate, which is more beneficial for postoperative recovery and to improve the quality of life in children ( 16 ). We obtained consistent results from the analysis of clinical data that complete resection was beneficial for patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on the influencing factors of surgical outcomes in patients with intractable epilepsy due to FCD has mostly focused on the analysis of clinical indicators such as seizure forms, electroencephalography, and surgical approaches. A complete resection of the assumed epileptogenic area was the only well-established factor for a satisfactory prognosis ( 5 7 ). The radiological studies related to FCD have been mainly committed to the summary of MRI features ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic literature review and meta-analysis identified complete resection of the lesion and location of the FCD lesion in the temporal lobe as predictors of favourable seizure outcome after surgery for MRI-detected FCD. Lesion extent, intracranial EEG use, or FCD histological type were not associated with postsurgical outcome 64. Correlation between the underlying genetic aetiology and postsurgical outcome remains to be determined 9…”
Section: What To Expect? Prognostic Aspectsmentioning
confidence: 97%
“…Up to 70% of patients with FCD and drug-resistant epilepsy, including children with severe epileptic encephalopathies, achieve a favourable seizure outcome after surgery 25 64. A recent retrospective multicentre cohort study of >9000 patients who underwent epilepsy surgery between 2000 and 2012 described the following findings: seizure outcomes were worst for FCDI and mMCD, possibly due to more diffuse structural abnormalities and a difficult-to-delineate epileptogenic zone and, consequently, to incomplete resections; children had a similar prognosis regarding seizure outcome to adults, but more children stopped the medication; temporal lobe surgeries had the best seizure outcomes, and a longer duration of epilepsy was associated with reduced chances of favourable seizure outcomes and drug withdrawal 23.…”
Section: What To Expect? Prognostic Aspectsmentioning
confidence: 99%
“…Resective surgery constitutes the rst-choice treatment for drug-resistant focal epilepsy due to FCD and other MCDs. The overall rate of favorable epilepsy outcome ranges between 64-70% at 12 months after surgery [3], [30], [31]. However, a signi cant proportion of MCD patients are not rendered seizure free after surgery.…”
Section: Introductionmentioning
confidence: 99%